Pelatihan Dalam Meningkatkan Pemahaman Akuntansi Keuangan Pada Siswa Siswi SMAN 2 Curup Rejang Lebong - Vivi Oktari; Dioni Lestari (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
State Senior High School (SMAN) 2 Rejang Lebong has the most students in the field of social sciences, especially accounting. The accounting department at SMAN 2 Rejang Lebong is one of the majors that has a positive response and has many enthusiasts, so the number of students majoring in accounting at SMAN 2 Curup Rejang Lebong is very significant. One of the problems faced by SMAN 2 Curup Rejang Lebong is that many students do not understand more deeply about accounting, more precisely about financial accounting, future career paths about accounting and updated regulations related to the basic concepts of accounting, financial recording & reporting. As a result, many students do not know about the latest rules regarding the basic concepts of accounting, especially financial accounting in financial recording and reporting and are confused about the next accounting career path. The method of implementing activities in community service is the lecture, interview, discussion, and evaluation method. The results of the training were an increase in the ability of students at SMAN 2 Curup Rejang Lebong plus education and lectures that could motivate students majoring in accounting to always update accounting rules and be ready to support future careers.